The Negotiation of Egyptian-American Identity in Miral Al-Tahawy's Brooklyn Heights - Syah, Ahfa Rahman; Damayanti, Fina (UIN Syarif Hidayatullah Jakarta, 2024)
This study aims to determine the problems and identity negotiations carried out by the protagonist, Hend, in the novel Miral al-Tahawy’s Brooklyn Heights. It is a qualitative research with descriptive analysis method by using Robert Stanton's Narrative Structure theory to show the main issues of the novel and Stuart Hall's identity theory to show Hend's identity negotiation. The results showed that the protagonist in her migration from Egypt to America experienced various identity problems, namely longing for the homeland, alienation, and identity crisis. All these problems encourage the protagonist to create efforts to negotiate between her past and present in several forms; using English to show her position as an American, carrying out dating traditions, drinking beer, dancing tango, and wearing open clothes. Hend's identity in America is not dominant to one side. She becomes half Arab and half American (a hybrid identity). The research also found that her romantic needs for an American man became the starting point of this American negotiation that can be considered as identity negotiation to claim her rights as an Egyptian-American, whose identity tends to be excluded from American citizens regardless the fact that she is American, but not white mainstream society.